2015
DOI: 10.1515/pomr-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Clocking In Turbines: Remarks On Physical Nature And Geometric Requirements

Abstract: The article discusses two issues relating to the clocking phenomenon in turbines, which are the physical course of stator wake deformation in rotor passages and its further interaction with downstream stator blades, and turbine geometry parameters which are believed to be most favourable for clocking. In both cases, the results presented in the article have made it possible to verify and reformulate the previously accepted opinions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Opting for this slight modification, the simulation of 1/8 sector of the whole geometry allowed satisfying the same periodicity of the rotating and stationary parts. The angular position of the first stage vanes and rotor blades was varied over the five equal distances within the angular interval a clock as proposed by Swirydczuk (2015)…”
Section: Clocking Effectsmentioning
confidence: 99%
“…Opting for this slight modification, the simulation of 1/8 sector of the whole geometry allowed satisfying the same periodicity of the rotating and stationary parts. The angular position of the first stage vanes and rotor blades was varied over the five equal distances within the angular interval a clock as proposed by Swirydczuk (2015)…”
Section: Clocking Effectsmentioning
confidence: 99%
“…Using potential flow formulation, Swirydczuk concluded that under an optimum clocking position, a special form of upstream wake vortices is shed within the blades passage which increases dynamic pressure and consequently outlet total pressure at blade throat. 22 Other wake tracking analyses can be referred to some researchers like Hodson, 23 Jouini et al, 24 Gombert et al, 25 and Arndt. 26 These researchers reported that the blade-wake interactions can be controlled by clocking mechanism to influence the aerodynamic performance of axial turbines, including turbine efficiency, profile loss, boundary layer transition, and development of the secondary flows.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, all over the world new trends were introduced. Flow channels, machines geometries (especially those of vanes and blades), and flow conducting solutions started to be redesigned since new machines should be as compact as possible, be characterized by low energy losses and the use of new materials and technologies is involved (Saren et al, 2000;Rzadkowski et al, 2003;Liptak, 2009;Balicki et al, 2010;Kang, 2014;Swirydczuk, 2015). To solve these problems rarely completely new unconventional methods are proposed, basing mostly on numerical methods (Marczyk, 1999;Sondak, Dorney, 2000;Bennett, 2005;Button, 2015;Manoha, 2017), sometimes also using neural networks (Gluch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%